Increasing Adolescent Awareness About The Hazards Of Smoking Through Interactive Education And Discussion - TITIK SUMIATIN; Wahyu Tri Ningsih; Aby Yazid Al Busthomy Rofi'i; Binti Jumali; Roudlotul Jannah; Moch Bahrudin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The period of adolescence is when childhood ends and adulthood begins. The adolescent age group, which is typically associated with the start of puberty, spans the ages of 12 and up. Adolescence is generally considered a period of good health. However, risky behaviors such as the use of harmful substances, poor diet or early sexual activity are topics that often arise. The method used in this community service activity is health education counseling. The counseling was accompanied by a question-and-answer discussion about the dangers of smoking. A total of 80 students of SMPN 2 Palang took part in community service activities. before counseling, the students' knowledge about the dangers of smoking was mostly good (40%), the students' attitudes towards smoking hazard behavior were all very negative (100%), and more than half of the students had never heard of the dangers of smoking (52.5%). Community service activities have a positive impact, namely increasing knowledge of the dangers of smoking. Furthermore, there is an increase in students who do not agree with smoking behavior. In general, there is a general decrease in smoking behavior after counseling.